2021
DOI: 10.3390/md19090485
|View full text |Cite
|
Sign up to set email alerts
|

Saringosterol from Sargassum fusiforme Modulates Cholesterol Metabolism and Alleviates Atherosclerosis in ApoE-Deficient Mice

Abstract: Dysregulation of cholesterol homeostasis is a major risk factor of atherosclerosis, which can lead to serious health problems, including heart attack and stroke. Liver X receptor (LXR) α and β are transcription factors belonging to the nuclear receptor superfamily, which play important roles in cholesterol homeostasis. Selectively activating LXRβ provides a promising strategy for the treatment of atherosclerosis. Here, we employed atherosclerotic apoE-knockout mice to evaluate the effects of saringosterol, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Note that manzamine A also presents anti-viral effects [36], which is particularly interesting considering that age-related cardiovascular diseases are frequently reported to be associated with certain bacterial and viral infections [41]. Conversely, saringosterol, a phytosterol derived from the marine algae Sargassum fusiforme, acts as a potent activator of the liver X receptor β, involved in cholesterol absorption, transport, and elimination [42]. Thus, it may impact the metabolism of lipids with a distinctive cellular target and specific metabolic transformation, inducing further pharmacological effects.…”
Section: Pre-clinical In Vivo Studies On Marine Compounds For Cvds Tr...mentioning
confidence: 99%
“…Note that manzamine A also presents anti-viral effects [36], which is particularly interesting considering that age-related cardiovascular diseases are frequently reported to be associated with certain bacterial and viral infections [41]. Conversely, saringosterol, a phytosterol derived from the marine algae Sargassum fusiforme, acts as a potent activator of the liver X receptor β, involved in cholesterol absorption, transport, and elimination [42]. Thus, it may impact the metabolism of lipids with a distinctive cellular target and specific metabolic transformation, inducing further pharmacological effects.…”
Section: Pre-clinical In Vivo Studies On Marine Compounds For Cvds Tr...mentioning
confidence: 99%
“…reported that saringosterol treatment reduced the burden of atherosclerotic plaques while having no negative effects on the liver of apoE-deficient rats. Saringosterol reduces cholesterol homeostasis disruption, influencing atherosclerosis’s progression [ 79 ]. However, asperlin is derived from the marine fungus Aspergillus versicolor LZD4403 and possesses antifungal and anti-inflammatory properties.…”
Section: Role Of Marine Drugs In Cvds Managementmentioning
confidence: 99%
“…24(S)-Saringosterol 24(S)-Saringosterol or (3β)-stigmasta-5,28-diene-3,24-diol is a marine phytosterol commonly isolated from the edible seaweed Sargassum fusiforme. 24(S)-saringosterol was shown to be a potential anti-atherosclerotic natural agent by lowering cholesterol and a selective LXR-β agonist [75,76]. An in vivo study of APPswePS1DE9 mice treated with 24(S)-saringosterol for 10 weeks revealed a slowing of cognitive decline based on enhanced spatial and object memory assessments.…”
Section: Lanosterolmentioning
confidence: 99%